"البلدية الإلكترونية" كآلية لتعزيز الشفافية الإدارية و المالية في البلديات الجزائرية - موفق, د/ عبد القادر (Sciences humaines, 2016)
تهدف هذه الدراسة إلى معرفة فوائد تطبيق البلدية الإلكترونية في الجزائر، خاصة في ظل الممارسات الإدارية البالية التي تزاولها  البلديات الجزائرية و التي تكاد تنعدم فيها الشفافية المالية و الإدارية .و قد اعتمد الباحث في ذلك على الدراسة الميدانية التي قام بها أثناء إعداده لرسالة الدكتوراه لعدد   من البلديات في ولاية باتنة للوقوف على واقع استخدام التكنولوجيا في البلديات الجزائرية بالإضافة إلى الإستفادة من تجارب بعض الدول في مجال تطبيق البلدية الإلكترونية.      و توصل الباحث لمجموعة من النتائج التي تؤكد ضرورة التحول السريع         إلى استخدام التكنولوجيا الحديثة في مختلف المجالات في البلدية، و بشكل خاص، التزام الشفافية في الإدارة المالية للبلدية و إعداد مختلف التقارير المالية و على رأسها الحساب الختامي (الحساب الإداري) و محاربة الفساد. الكلمات الدالة : البلدية، البلدية الإلكترونية، الإدارة المالية، الشفافية، المساءلة، الحكم الراشد. The presentpaper aims at summarizing the main challenges and issues related to strengthening transparency, governance and Institutions in the Algerian municipalities through applying the “e municipality” concept. The recent social and political evolution in the country has highlighted the need for reform in these matters as one of the local priorities. . The reforms about transparency, accountability and civil society participation, are expected to be very important in today’s municipality life and must be achieved soon by applying the e municipality concept.  In order to achieve this, the researcher relied on a recent PhD study which included many municipalities in Batna city, as well as on the experience of many “e municipalities” in different countries.       The study concluded that it’s very important to make an early change to the municipalities in Algeria in order to realize many benefits and achieve the goals defined as: transparency, governance and financial reporting as well as fighting corruption. Key words: municipality, e municipality, financial management, transparency, accountability, good governance